2007
DOI: 10.2139/ssrn.1329308
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Pricing and Reimbursement Policies in Canada

Abstract: This paper describes and assesses pharmaceutical pricing and reimbursement policies in Canada, considering them in the context of the broader policy and market environment in which they operate, and investigating their role in contributing to Canada's achievements in meeting a range of objectives relating to the pharmaceutical policy. The federal government regulates prices of patented pharmaceutical products with the objective of protecting consumers against excessive prices. Regulation has very likely been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 36 publications
1
25
0
3
Order By: Relevance
“…Mizik (Mizik & Jacobson, 2004) found that physician detailing and complimentary drug samples both have a positive and statistically significant effect on the prescribing behaviors of physicians. These results are strongly grounded in past research, as several studies found similar findings (Bingle, O'Connor, Evans, & Detamore, 1991, Wazana, 2000, Paris & Docteur, 2006.…”
Section: Literature Reviewsupporting
confidence: 87%
See 1 more Smart Citation
“…Mizik (Mizik & Jacobson, 2004) found that physician detailing and complimentary drug samples both have a positive and statistically significant effect on the prescribing behaviors of physicians. These results are strongly grounded in past research, as several studies found similar findings (Bingle, O'Connor, Evans, & Detamore, 1991, Wazana, 2000, Paris & Docteur, 2006.…”
Section: Literature Reviewsupporting
confidence: 87%
“…In a price-volume agreement, the manufacturer and the payer may agree upon a threshold based on the manufacturer's estimate of sales (Paris & Docteur, 2006). If the total sales exceed the threshold value, the manufacturer pays a proportion, α, 0≤α≤1, of the excess sales to the payer.…”
Section: Model Structure and Assumptionsmentioning
confidence: 99%
“…To incentivize the pharmaceutical industry to do business in Quebec, this legislation was introduced in 1994 and allows brand name drugs to qualify for reimbursement for 15 years after inclusion on the provincial formulary, even if their patent expires and the generic version becomes available on the market. This in turn provides two to five additional years of patent protection (Gagnon 2011;Paris and Docteur 2006). However, in an attempt to control prescription drug costs, the government recently abolished the 15-year rule as part of the 2013/2014 budget (Marceau 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Known under a variety of names, a common element of these product listing agreements (PLAs) is the negotiation of confidential prices that are typically achieved through rebates that may or may not be tied to drug expenditures, utilization patterns or health outcomes. Though Canadian hospitals have long used confidential purchasing arrangements, provincial drug plans rarely negotiated confidential price rebates before 2006 (Gorecki 1992;Morgan et al 2003;Paris and Docteur 2007). In recent years, however, some provinces have begun to use PLAs routinely, and in 2010, a Pan-Canadian Purchasing Alliance was established to coordinate PLA negotiations for some new medicines on behalf of participating provinces (Lynas 2010).…”
Section: Résumémentioning
confidence: 99%